Power Scheduling Strategy of Grid Tied PV/Wind/BESS/ DG for Optimal Time-Of-Use Electricity Pricing - Sushil Kumar Bhoi, Manas Ranjan Nayak, Kumari Kasturi (International Journal of Control and Automation, 2020)
The evaluation of classical grid to smart grid has become a necessity and Renewable Energy Sources are an important part of smart grid. In the electricity markets, there is a strong correlation between market participants’ (suppliers and consumers) behavior and their profits. Solar, wind turbine, battery, Diesel Generator (DG) and grid have been considered as power supply sources for two suppliers. The load demand of two areas of Odisha, India i.e., consumer-1 and consumer-2 in a day during both summer and winter season have been considered. In this work, game theory technique has been proposed to determine optimum hourly clearing electricity price in electricity grid for maximizing suppliers and consumers benefits with the best reliability of the system. To solve this problems, a time and seasonal varying load along with seasonal variation of generation (solar and wind) curve has been considered.